A novel missense mutation in the gene FZD6 underlies autosomal recessive nail dysplasia. (5th October 2012) - Raza, S.I.; Muhammad, N.; Khan, S.; Ahmad, W.
Summary Background Inherited isolated nail anomaly manifesting with onychauxis and onycholysis is a rare condition, caused by mutations in the gene FZD6, encoding membrane‐bound Wnt receptor protein. Objectives To search for sequence variants in the gene FZD6 in three individuals of a consanguineous family exhibiting features of nail dysplasia. Methods Linkage in the family was searched by genotyping microsatellite markers linked to the gene FZD6, mapped at chromosome 8q22.3. Exons and splice junction sites of the gene FZD6 were polymerase chain reaction amplified and sequenced in an automated DNA sequencer. Results DNA sequence analysis revealed a novel homozygous missense mutation (c.1266G>A; p.Gly422Asp) located in the transmembrane domain of the protein FZD6. Conclusions The missense mutation (p.Gly422Asp), identified here, is only the third mutation detected in the gene FZD6.